Drūkšiai lake (Ignalina NPP cooler) dynamics of the ichthyocenose - Švitra, Donatas; Žemaitis, Giedrius (Lietuvos matematikos rinkinys, 2012)
This article describes the existing Drūkšiai lake ecosystem. After setting up the integrity of this mathematical model (2.1)–(2.2) thermal loads there are simulated Drūkšiai Lake dynamics of the ichthyocenose. It is done by using Runge–Kut IV method from this simulation program “ModelMaker”. The model numerical solutions of F1–F9 are compared with experimental data for the monitoring of fish. This dynamics is simulated by the year 2010 and projected to 2020.